Clostridium difficile infection: a Serbian single-center experience - Milos Korac; Ivana Milosevic; Marko Markovic; Natasa Popovic; Milena Ilic; Aleksandar Markovic; Jelena Nikolic; Djordje Jevtovic (Journal of Infection in Developing Countries)
Introduction: Clostridium difficile infection (CDI) is the most common cause of hospital-acquired diarrhea. Severity of CDI is associated with advanced age and co-morbidities. The clinical spectrum varies from mild watery diarrhea to severe fulminant pseudomembranous colitis with complications. Methodology: This study conducted over a six-year period (2008 to 2013) included 510 patients treated at the University Hospital for Infectious and Tropical Diseases in Belgrade, Serbia. In patients with a history of previous hospitalization and/or treatment with antimicrobial agents who developed diarrhea, the diagnosis was established with rapid tests for C. difficile toxin A and B and by stool culture for C. difficile (454 patients) or by endoscopic examination and histological analyses of the biopsy samples taken from the colonic mucosa (56 patients). Results: The mean age of patients was 67.71± 13.34 years. A total of 67.8% patients were older than 65 years. Over half (58.7%) of the patients were female. 93% had been previously hospitalized and/or had surgical interventions, during which they had been treated with antibiotics. In the clinical presentation spectrum, pseudomembranous colitis occurred in 51.0% .The mean duration of illness after the introduction of specific antibiotic therapy was 7.10 ± 4.88 days. Complications developed in 14 patients. The disease relapsed in 43 (8.4%). Thirty-two (6.3%) patients died, mostly due to co-morbidities. Conclusions: CDI is the most important cause of hospital-acquired diarrhea in Serbia. The disease mainly affects elderly patients with co-morbidities. The incidence of complications is low and prognosis is age dependent and related to pre-existing diseases.